1990
DOI: 10.1017/s0033583500005588
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of cytochrome oxidase

Abstract: This article tries to be a compact summary of some recent research on cytochromecoxidase (EC 1.9.3.1), an important enzyme in membrane bioenergetics. Cytochrome oxidase is the terminal catalyst of the mitochondrial respiratory chain. It uses the electrons flowing through the chain to reduce oxygen molecules to water. Four electrons and four protons are consumed in the reduction of O2to two molecules of water (Fig. 1). Cytochrome oxidase contains four redoxactive metal centres. Two of these are copper atoms, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
330
0
5

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 405 publications
(346 citation statements)
references
References 116 publications
11
330
0
5
Order By: Relevance
“…In contrast, the phenylalanine ring may be orientated parallel to the membrane, effectively interrupling the water array. Saraste [20] and Iwata et al [5] have suggested that an invariant ghltamic acid residue in helix VI of subunit I, Glu212 2 may be involved in the mechanism of proton translocation. In agreement with this, its change to cysteine was recently shown to inhibit proton translocation in the reconstituted cytochrome ho:~ enzyme from E. colt (wherc it is Glu'-'s¢~), with much less effect on electron transfer [17].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the phenylalanine ring may be orientated parallel to the membrane, effectively interrupling the water array. Saraste [20] and Iwata et al [5] have suggested that an invariant ghltamic acid residue in helix VI of subunit I, Glu212 2 may be involved in the mechanism of proton translocation. In agreement with this, its change to cysteine was recently shown to inhibit proton translocation in the reconstituted cytochrome ho:~ enzyme from E. colt (wherc it is Glu'-'s¢~), with much less effect on electron transfer [17].…”
Section: Resultsmentioning
confidence: 99%
“…The COl protein, which is involved in the mitochondrial respiratory chain, has been divided into 25 structural regions falling into five different categories (Saraste, 1990;Lunt et a!., 1996). The sequence variability found among the Hegeter species is maximum in the last 120 nucleotides of fragment 2, which is coincident with the 3' end of the gene.…”
Section: Discussion Sequence Variationmentioning
confidence: 99%
“…The enzyme accepts electrons from ferrocytochrome c and mediates transmembrane electron transfer from the cytoplasmic side to the matrix side of the inner mitochondrial membrane and reduces dioxygen at the binuclear site [1,2]. The primary electron acceptor in Cc0 is the Cu, or heme a site near the cytosolic side and electron transfer takes place to the binuclear heme a~-Cu, active center [3,4].…”
Section: Introductionmentioning
confidence: 99%